The Rate of Clinical Outcomes in Atrial Fibrillation according to Antithrombotic Strategy: The COOL-AF Registry - Rungroj Krittayaphong; Arjbordin Winijkul; Komsing Methavigul; Poom Sairat; C. O. O. L.-A. F. investigators (Cardiovascular Therapeutics)
Background. Ischemic stroke/transient ischemic attack (TIA), major bleeding, and death are common outcomes in atrial fibrillation (AF) patients, so appropriate antithrombotic therapy is crucial. The objective of this study was to investigate the rate of ischemic stroke/TIA, major bleeding, and death compared among AF patients who received oral anticoagulant (OAC) alone, antiplatelet alone, or OAC plus antiplatelet. Methods. Prospective data from the COOL-AF Registry (Thailand’s largest multicenter nationwide AF registry) were analyzed. Clinical, laboratory, and medication data were collected at baseline and during follow-up. Clinical outcomes, including ischemic stroke/TIA, major bleeding, and death, were collected. Results. There were 3,148 patients included. Mean age was 68.1±10.8 years and 1,826 (57.7%) were male. AF was paroxysmal in 998 (31.7%), persistent in 603 (19.2%), and permanent in 1,547 (49.1%). The mean follow-up duration was 25.7±10.6 months. The median rates of ischemic stroke/TIA, major bleeding, and death were 1.49 (1.21-1.81), 2.29 (1.94-2.68), and 3.89 (3.43-4.40) per 100 person-years. Antiplatelet alone, OAC plus antiplatelet, and OAC alone were used in 582 (18.5%), 308 (9.8%), and 2,258 (71.7%) patients, respectively. Antiplatelet alone significantly increased the risk of ischemic stroke/TIA and death compared to OAC alone. OAC plus antiplatelet significantly increased the risk of death compared to OAC alone. Conclusions. Antiplatelet was used in 890 (28.3%) AF, of whom 582 (18.5%) received antiplatelet alone, and 308 (9.8%) received antiplatelet and OAC. OAC plus antiplatelet significantly increased the risk of death without additional stroke prevention benefit. Antiplatelet alone should not be used in patients with AF.